The Influence of Digital Leadership and Organizational Culture on Employee Performance in the Industry 4.0 Era - O. Olivia; H. Haedar; Suhandra Makkasau (Manunggal Halim Jaya, 2026)
The rapid development of digital technology in the Industry 4.0 era has transformed organizational work patterns, including in the banking sector, which is required to adapt to digital transformation. In this context, employee performance has become a crucial factor in supporting organizational success. This study aims to analyze the influence of digital leadership and organizational culture on employee performance at Bank Sulselbar Masamba Branch in the Industry 4.0 era. This study employed a quantitative research approach using primary data collected through questionnaires distributed to respondents. The study population consisted of all active employees of Bank Sulselbar Masamba Branch, totaling 34 employees in the branch. A saturated sampling technique was applied, in which the entire population was selected as the research sample for this study. The data were analyzed using IBM SPSS Statistics Version 26 through validity and reliability tests, multiple linear regression analysis, the t-test (partial), and the F-test (simultaneous). The results indicate that digital leadership has a positive and significant effect on employee performance, with a significance value of 0.000 (p < 0.05). Organizational culture also has a positive and significant effect on employee performance, with a significance value of 0.003 (< 0.05). Simultaneously, digital leadership and organizational culture have a positive and significant effect on employee performance, as indicated by an F-value of 39.622 and a significance value of 0.000 (p < 0.05). These findings suggest that improving employee performance is determined not only by the effective utilization of digital technology but also by leadership capabilities in managing organizational change and an organizational culture that supports innovation and adaptation to digital transformation.